A Annona emarginata é capaz de acumular metais pesados essenciais sem causar danos ao seu metabolismo? - Baron, Daniel (2017)
This study aimed to evaluate if ionic strength variation causes differential accumulation of heavy metals in plants of Annona emarginata (Schltdl.) H. Rainer var. ‘terra-fria’, modifying gas exchange and dry matter production. The seedlings were cultivated under different ionic strengths of the ‘Hoagland and Arnon’s’ nutrient solution (75% I, 50% I and 25% I). At 180 days after the application of the treatments, the effects of the essential heavy metals on the physiological parameters and foliar ionic concentration were assessed. The leaf gas exchanges and vegetative growth were affected by the variation in the essential heavy metals, with positive effects on the plants that were treated with 75%I. The seedlings that were grown under 75% I presented higher concentrations of Zn (24.2mg kg-1). On the other hand Fe (453mg kg-1) e Mn (803.5mg kg-1) accumulated more under 25% I, but gas exchanges and vegetative growth were reduced, compared to 50%I and 75%I. We can conclude that the ionic strength variation alters gas exchange and the dry matter accumulation, causing differential accumulation of Fe, Mn and Zn in A. emarginata, occurring inverse relationship between increased ionic strength and Fe and Mn content, besides directly relationship to the Zn content.